Peranan Koperasi Unit Desa (KUD) Dalam Meningkatkan Pendapatan Petani - Muhammad Buchari Sibuea (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
One of the government and private effort to improve people's welfare particularyly to improvefarmer's income in villagea is to activate cooperative life particularly Village Cooperation Unit (KUD), and more specificly, is Agriculture Cooperation. Thr objevtive of this research was to know the efficiency level of oil palm farming organized by farmers together with cooperative. Theoratically some social economic variables have been known influences the rate of farmer's income, therefore in this research three social variables, such as the level of cooperation service to farmers, level of members participation to the cooperation and level off freindship among farmers with cooperation were studied. List of questions divided into 40 family's leader or farmer members of KUD which become samples of this research. Analysis models were used production function models of Coob-Dauglass and Output Input Ratio (OIR) models and they calculation helped by computer Microstaat Programs. It was concluded that level of participation and frienship pertially were significantly to the income's rate (in 95% level of confidence) meanwhile variable of cooperation services level were not significant. Simultaneously, the three factors gave very significant contribution to improve farmer's income of cooperationmembers, where R-square was 0.9726 so that very significant in confident level of 99%. It's also conclude that the biggestcontribution given by variable of frienship level because it's have the biggest elasticity, 2.847. Efficiency level of farming effort of the farmers is very well or very feasible with the average of OIR rate of 19.23 or 19.23% that so farexceed of properly value 1 or 100%. This research process among institution since the contribution was significantly improving the farmers income.Keyword : Cooperation, Farmers income.